FTIR assessment and investigation of synthetic antioxidant on the fuel stability of Calophyllum inophyllum biodiesel. (1st December 2017) - Mohamed Shameer, P.; Ramesh, K.
Abstract: 'Fuel Stability' is one of the most significant properties of biodiesel, which insists the biodiesel stability during prolonged storage period. Poor resistance to oxidation process is the main hurdle for biodiesel commercialization in the global fuel market. Biodiesel degradation by the products yielded from oxidation process may deprive the fuel properties and obviously engine performance. Dosage of synthetic antioxidants is an appropriate method for improving the fuel stability of biodiesel. The present research work investigates the effects of tert -butyl hydroquinone (TBHQ) antioxidant additive concentrations on the oxidation stability, long-term storage stability and thermal stability of Calophyllum inophyllum biodiesel. Fourier Transform Infra-red (FTIR) spectroscopy was used to characterize the oxidation variability of biodiesel, following the FTIR spectrum regions of CH and OH bonds for various concentrations of TBHQ. Dosage of TBHQ at 1000 ppm concentration (B100A3) with pure biodiesel enhances the oxidation stability by 94.658%, storage stability by 14.466% and thermal stability by 37.269%; meanwhile further dosage of antioxidant deteriorates the formation of hydrophobic and hydrophilic clusters between antioxidant and biodiesel compounds, which is characterized through FTIR spectrum. It is concluded that by dosing 1000 ppm of TBHQ antioxidant with Calophyllum inophyllum biodiesel could enhance the storage period.